Enzyme relationships in a sorbitol pathway that bypasses glycolysis and pentose phosphates in glucose metabolism. - Jeffery, J (1983)
A pathway from glucose via sorbitol bypasses the control points of hexokinase and phosphofructokinase in glucose metabolism. It also may produce glycerol, linking the bypass to lipid synthesis. Utilization of this bypass is favored by a plentiful supply of glucose--hence, conditions under which glycolysis also is active. The bypass further involves oxidation of NADPH, so the pentose phosphate pathway and the bypass are mutually facilitative. Possible consequences in different organs under normal and pathological, especially diabetic, conditions are detailed. Enzymes with related structures (for example, sorbitol dehydrogenase and alcohol dehydrogenase, and possibly, aldehyde reductase and aldose reductase, respectively) are linked functionally by this scheme. Some enzymes of the bypass also feature in glycolysis (aldolase and alcohol dehydrogenase), and these enzymes, with the reductases involved, are proteins known to occur in different classes or multiple isozyme forms. Two of the enzymes (aldolase and alcohol dehydrogenase) both involve classes with and without a catalytic metal (zinc). The existence of parallel pathways and the occurrence of similar enzymic steps in one pathway may help to explain the abundance and multiplicity of enzymes such as reductases, aldolases, and alcohol dehydrogenases.